IMPLEMENTASI KEBIJAKAN PENGELOLAAN LAHAN PERTANIAN PANGAN BERKELANJUTAN DI KABUPATEN MADIUN, JAWA TIMUR - Nur’Aini, Latifah; Nugroho, Sigit Sapto; Pradhana, Angga Pramodya (Jurnal Ilmiah Dinamika Hukum, 2026)
This study aims to analyze the implementation of the Sustainable Food Crop Land (LP2B) management policy in Madiun Regency based on Regional Regulation Number 3 of 2020 and identify factors inhibiting its implementation, as well as formulate alternative solutions to strengthen the policy in supporting agricultural land sustainability and regional food security. This study uses an empirical legal method (empirical juridical) with a qualitative descriptive approach. Primary data were obtained through in-depth interviews with the Department of Agriculture, and farmers, as well as field observations, while secondary data were obtained through a study of laws and regulations and policy documents. The analysis was conducted by examining aspects of communication, resources, disposition, and bureaucratic structure in policy implementation, using triangulation techniques to ensure data validity. The results show that LP2B implementation is not optimal. The main obstacles include farmers' low understanding of legal provisions, limited human resources and budget, weak cross-sectoral coordination, and economic pressures and high land sales prices. In addition, the national target of fulfilling 87% of Raw Paddy Land adds to the complexity of implementation at the regional level. Strengthening implementation requires improving legal communication, strengthening institutional capacity, synchronizing policies with spatial planning, and a participatory approach that actively involves farmers.